THE EFFECT OF USING COMIC MEDIA TOWARD STUDENTS PREPAREDNESS IN ENCOUNTERING LANDSLIDE DISASTER AT SDN 1 SUKAWANA KARANGASEM REGENCY - Wedri, Ni Made; Amelia, Amelia; Rasdini, I Gusti Ayu Ari (Universitas Respati Yogyakarta, 2021)
The aim of this research is to know the effect of educational learning through comic media towards elementary students’ awareness in encountering disaster. The type of this research is Pre-Experimental Design with One-Group Pretest-Posttest design using total sampling. There are 57 samples and the data collection was done by fill the questionnaire of landslide disaster preparedness. The result is showing the average of awareness before the students was given an awareness education is 69,68 and after they were given the education the average of awareness is76,63with difference average before and after treated is 6,94.Hypothesis testing is implemented by paired t statistic test with p-value of 0.001 (α = 0.05). It can be concluded that, there are effect occurred of the awareness education given to the student through comic media in SDN 1 Sukawana. Keywords: Landslide disaster; Preparedness; Comic media